2014
DOI: 10.1111/pme.12379
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Response to the Thermal Grill Illusion in Chronic Pain Patients

Abstract: This preliminary data suggest that the thermal grill response may provide insights into pain sensitivity that are not detected by conventional thermal quantitative sensory testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…The reinstatement of body representation through self-touch has also been demonstrated in a case report involving a stroke patient with somatoparaphrenia, the denial of ownership of a limb (van Stralen et al, 2011). Interestingly, patients with chronic pain report a weakened heat sensation by the cool finger during the thermal grill illusion compared with pain-free controls (Sumracki et al, 2014). An altered central integration of ascending pain and temperature signals was concluded by the investigators, given that no significant difference was observed in thermal thresholds amongst the pain and pain-free groups.…”
Section: Tactile Sensationmentioning
confidence: 84%
“…The reinstatement of body representation through self-touch has also been demonstrated in a case report involving a stroke patient with somatoparaphrenia, the denial of ownership of a limb (van Stralen et al, 2011). Interestingly, patients with chronic pain report a weakened heat sensation by the cool finger during the thermal grill illusion compared with pain-free controls (Sumracki et al, 2014). An altered central integration of ascending pain and temperature signals was concluded by the investigators, given that no significant difference was observed in thermal thresholds amongst the pain and pain-free groups.…”
Section: Tactile Sensationmentioning
confidence: 84%
“…Kenshalo et al, 1982;Khasabov et al, 2001). However, very few studies have directly analysed the changes in TGIP in patients with pain (Heavner et al, 1997;Morin et al, 2002;Sumracki et al, 2014). the parabrachial nucleus, periaqueductal grey area, raphe nuclei) are also involved in thermoregulation (Romanovsky, 2007;Morrison and Nakamura, 2011).…”
Section: Beforementioning
confidence: 99%
“…Our previous results, showing that the administration of an infra-anaesthetic dose of ketamine, an NMDA receptor antagonist with preferential anti-hyperalgesic effects, induces a specific decrease in TGIP (Kern et al, 2008a), are consistent with this hypothesis. However, very few studies have directly analysed the changes in TGIP in patients with pain (Heavner et al, 1997;Morin et al, 2002;Sumracki et al, 2014).…”
Section: Beforementioning
confidence: 99%
“… 12 Thus, although the TGI does not involve nociceptive input, it activates the nociceptive system at a higher central level of processing. The underlying processes have already been related to clinically altered pain processing, 44 highlighting the importance of sensory integration for pain perception.…”
Section: Introductionmentioning
confidence: 99%